University Students’ Views on the Challenges Faced by Students with Difficulties - Sonia Ruiz de Azua; Naiara Ozamiz-Etxebarria; Maitane Picaza; Eneritz Jiménez-Etxebarria; Nahia Idoiaga (Social Sciences)
Introduction: The pursuit of an inclusive university is rooted in the commitment to ensuring equal opportunities within the educational landscape. Over the years, the notion of “inclusion” has significantly evolved, becoming a central aspect of individual rights. This shift has led to the development of various models and guidelines to provide equitable treatment to all students. Objectives: This study aims to explore the perceptions of students regarding inclusive education at a university in the north of Spain. It seeks to understand the reasons behind these perceptions, providing insights into the effectiveness of the current inclusion strategies. Methods: We conducted an online survey distributed across various faculties at a university in the north of Spain, with participation from 519 students. The data collected from the survey were coded and subjected to statistical analysis using SPSS version 28 to generate descriptive and comparative statistics. Results: The findings reveal that 2.5% of the students have experienced discrimination at some point, with 2.9% attributing such discrimination to their peers. Furthermore, 25% of the respondents acknowledged the presence of discrimination initiated by the university itself. Despite these challenges, a significant majority (88.8%) recognize the importance of inclusive education. However, 43.4% of the participants noted that the attitudes of some faculty members towards inclusion were suboptimal. Additionally, 82.9% of the respondents believe in the necessity of enhancing collaboration within the entire educational community to foster better inclusion. Discussion and Conclusions: Overall, the students view the university as inclusive but identify a gap in the awareness and training necessary for achieving true equality. These findings indicate a need for heightened visibility of resources and the provision of further training and workshops. Although the response rate to the survey was relatively low, further research might benefit from engaging a broader spectrum of student voices, especially those from non-normative or divergent backgrounds, to deepen the understanding of inclusivity at the university.